PENILAIAN KAPASITAS DAN PEMANFAATAN GAS METANA DI TPA BAGENDUNG CILEGON, INDONESIA - Hasianetara, Sarah; Sodri, Ahyahudin; Mugi Astuti, Lina Tri (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2023)
Cilegon only relies on one final disposal site, namely the Bagendung Landfill, which annually receives up to 24.742,80 tons of waste from the population of Cilegon. This amount has an impact on the amount of waste generated and affects the length of time Bagendung Landfill can operate. The process of degradation of organic waste material at the landfill produces landfill gas which includes methane gas (CH4) and carbon dioxide gas (CO2) thereby contributing to GHG (Green House Gas) emissions. This study aims to analyze the remaining operation time frame of and the production of methane gas produced from the waste disposal process at Bagendung Landfill, also its contribution to GHG emissions. This research was started by surveying to find out the waste generation that goes to the landfill and the remaining land area to receive municipal waste. This study used LandGEM version 3.02 software to calculate methane gas production resulting from the landfill waste degradation process. Due to the predicted waste collected in 2024 reaching 281,984.90 m3, Bagendung Landfill can only be utilized until 2024. The emission impact can be reduced by utilizing 1.527.184,57 m3 of methane gas to produce 1.65 GWh as an alternative to electrical energy which is very helpful in meeting the electricity needs of Cilegon City. This research indicates that Bagendung Landfill will not be able to maintain its capacity as it will be reached one year earlier than designed. Utilizing landfill methane gas increases the environment's quality by avoiding 25.471,47 tCO2eq of GHG emissions. Moreover, it can continue after the landfill is closed. Keywords: landfill; waste generation; methane gas production; emission